Achilles Tendon Repairs: Identification of Risk Factors for and Economic Impact of Complications and Reoperation. (January 2023) - Trivedi, Nikunj N.; Varshneya, Kunal; Calcei, J. Blake; Lin, Kenneth; Sochaki, Kyle R.; Voos, James E.; Safran, Marc R.; Calcei, Jacob G.
Background: Compared with nonoperative management, Achilles tendon repair is associated with increased rates of complications and increased initial healthcare cost. However, data are currently lacking on the risk factors for these complications and the added healthcare cost associated with common preoperative comorbidities. Hypothesis: Identify the independent risk factors for complications and reoperation after acute Achilles tendon repair and calculate the added cost of care associated with having each preoperative risk factor. Study Design: Retrospective cohort study. Level of evidence: Level 3. Methods: A retrospective review of a large commercial claims database was performed to identify patients who underwent primary operative management for Achilles tendon rupture between 2007 and 2016. The primary outcome measures of the study were risk factors for (1) postoperative complications, (2) revision surgery, and (3) increased healthcare resource utilization. Results: A total of 50, 279 patients were included. The overall complication rate was 2.7%. The most common 30-day complication was venous thromboembolism (1.2%). The rate of revision surgery was 2.5% at 30 days and 4.3% at 2 years. Independent risk factors for 30-day complications in our cohort included increasing age, hyperlipidemia, hypertension, female sex, obesity, and diabetes. Independent risk factors for revision surgery within 2 years included female sex, tobacco use, hypertension, obesity, and the presence of any postoperative complication. The average 5-year cost of operative intervention was 17, 307. The need for revision surgery had the largest effect on 5-year overall cost, increasing it by 6776.40. This was followed by the presence of a postoperative complication (3780), female sex (3207.70), and diabetes (3105). Conclusion: Achilles tendon repair is a relatively low-risk operation. Factors associated with postoperative complications include increasing age, hyperlipidemia, hypertension, female sex, obesity, and diabetes. Factors associated with the need for revision surgery include female sex, hypertension, obesity, and the presence of any postoperative complication. Female sex, diabetes, the presence of any complication, and the need for revision surgery had the largest added costs associated with them. Clinical Relevance: Surgeons can use this information for preoperative decision-making and during the informed consent process.